Education Information Professionals - Lasić-Lazić, Jadranka (Array, 2005)
This paper deals with education of information professionals at the Faculty of Philosophy in Zagreb. The changes affecting the environment of studies are analyzed as well as the changes that affect the curricula. The analisys tries to find the path which the professionals should follow to prepare themselves for ongoing and future changes. The basic ides of the analysis and changes are to get closer to international academic standards and thus provide mobility of students and postgraduates in European academic context and make them attractive in the labor market.